Algorithm for acute pancreatitis diagnostics and treatment in pregnant women - Feleshtinskii, Ia.; Pavliv, T. (Journal of Education, Health and Sport, 2023)
Introduction. The problem of early diagnostics and treatment of pregnant women with acute pancreatitis (AP) remains far from being solved despite a significant number of clinical trials [1, 2, 3]. There are still no AP specific recommendations with regard to early diagnostics and treatment. Recently, some sporadic reports on the determination of serum pancreatic elastase levels in pregnant women diagnosed with acute pancreatitis were recorded. At present, there are no available guidelines for the treatment of acute pancreatitis and its complications during pregnancy, emphasizing the role of minimally invasive surgical interventions. Objective of the study: improve the efficiency of acute pancreatitis diagnostics and treatment in pregnant women. Materials and methods. The analysis of diagnostic results and complex treatment of 123 pregnant women was carried out. The treatment group consisted of 61 pregnant women with acute pancreatitis for the period from 2012-2018, using the developed diagnostic and treatment algorithm and the experimental group included 62 pregnant women, from 2006 to 2012, using traditional methods of treatment and diagnosis. Results of the study. According to the results of the study, it can be noted that traditional ways of acute pancreatitis treatment do not take into account the limitations in the use of a number of diagnostic methods in pregnant women, as well as the peculiarities of treatment tactics in different trimesters of pregnancy. Meanwhile, the developed diagnostic and treatment algorithm has significant advantages, i.e. - early diagnostics based on the determination of elastase 1 at all stages of patient management. It allows detecting acute pancreatitis at an early stage of the disease in 100% of patients in the main group, compared to 48.4% in the comparison group. - Early use of conservative therapy due to early diagnostics. A positive effect in conservative therapy was achieved in 44.3% of patients in the main group, compared to 33.9% in the comparison group. - 50.8% of patients in the study group managed to limit themselves to minimally invasive methods of treatment, such as punctures and drainage of fluid formations, endovideoscopic methods of sequestrectomy compared to 46.8% in the comparison group. - The widespread use of minimally invasive treatment methods allowed to reduce the number of open surgical interventions in the main group up to 4.9% vs. 38.7% in the comparison group, and to avoid mortality vs. 3.2% in the comparison group. Conclusion. The developed diagnostic and therapeutic algorithm for acute pancreatitis in pregnant women in comparison with traditional methods of diagnostics and treatment allows to detect acute pancreatitis at an early stage of the disease. Ensure the effect of conservative therapy in 44.3% versus 33.9%, and to achieve the effect of minimally invasive surgical interventions in 50.8% against 46.8%, open surgical interventions in 4.9% against 38.7% of the comparison group, and to avoid mortality against 3.2% of the comparison group.